Financial Sector Development in Brunei Darussalam: Depth, Access, and Efficiency: A Comparative Analysis - Biswa Nath Bhattacharyay; Madhurima Bhattacharyay (Center for Economic Studies and ifo Institute (CESifo), 2022)
Financial sector development plays an important role in promoting economic growth and welfare of the citizen of a country. On the other hand, financial sector instability or vulnerability, can adversely affect the economic growth and cause major disruptions in the country. This paper examines the financial sector development of Brunei Darussalam in terms of depth, access and efficiency during 2014-2018 based on 24 indicators. This paper starts with the examination of the role of the financial sector in the economic development and financial sector stability and reviews the major literature in this area. A discussion on the policies and strategies for the financial sector development and its regulator, Brunei Darussalam Central Bank (BDCB) and the structure of the financial sector of Brunei Darussalam are presented. Lastly, the paper discusses the major prospects and challenges faced by the banking sector as well as the recommendations. The analysis of the aforementioned indicators shows that the performance of Brunei Darussalam in terms of access to banks and financial inclusion had been, on an average, significantly better than its most peers among Association of Southeast Asian Nations (ASEAN) and Gulf Cooperation Council (GCC) countries. In terms of depth and intermediation, the country, however, remained lower throughout the study period compared to its most ASEAN and GCC countries. The efficiency of banking sector, on an average, remained at a moderate level with most indicators lower compared to several ASEAN and GCC peers. There is a scope for further financial sector development through enhancing depth and efficiency of the banking sector and the development of efficient bond and stock markets. This could bring significant benefits for Brunei Darussalam including enhanced growth.
Keywords: G20; D53; O16; E44; G21; G32; 330; banking and financial sector development and indicators; economic growth; financial stability; financial depth; access and efficiency; Brunei Darussalam; ASEAN and GCC countries; fintech companies